PEMIKIRAN AL-BUTHI TENTANG PROBLEMATIKA DAKWAH - Nanik Mujiati; Lukman Hakim (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
This article focuses on examining the thinking of prominent religious scholars of Syria, Muhammad Sa’id Ramadhan al-Buthi in his work entitled Hakadhā Falnad’u Ilā al-Islam related problem of da’wa which is getting stronger now. Example phenomena of distrust fellow muslim, dichotomy between the Islamic state and the heathen state, and muslim interactions with non-muslim families. That problematic da’wah now very easy to meet in various rare meeting houses, increasingly spread easily through social media. so that, this article want to further review in Muhammad Sa’id ramadhan alButhi’s view of what has been known as moderat religious scholars, and is one of the referrals many da’i in Indonesia. And it can give a new perspective in snapshot and responding to comprehensive about various da’wa phenomena of extremes.